Revolution in Asian Food Supply Chains: Implications for Farmers and Consumers - Reardon, Thomas; Minten, Bart; Chen, Kevin Z. (2011)
Thomas Reardon, IFPRI/MSU Joint Program on Markets in Asia Bart Minten, IFPRI Kevin Chen, IFPRI